Liberdade vigiada: um estudo sobre o processo criativo em dança contemporânea. - Paes, André Duarte (2015)
This paper aims to a study of the creative process in contemporary dance from the freedom with regard to the socio-political behavior of the modern world. The dissertation is dedicated to the study of behavioral relationships in this social context, dialogue with dance, research and understanding of interdisciplinary elements, adding different aesthetic settings for developing choreographic trends and their representations of the artistic work. Therefore, the research was systematized from procedures to map significant theories of freedom whose reference transits Foucault, Vattimo, among others, and through these, there were dance experiments resulting in a finished product research a show titled Freedom Watched . The result reveals a possibility of linking social experiences, art and dance, showing that creative processes can be used to observed elements by studying the analysis of these languages for the development of new jobs in this creative potential, reflective, observant and transforming that art comes building, this work with dance. Keywords: Freedom; Dance; Socio-political Behavior; Criative Process.